2021
DOI: 10.1186/s12890-021-01633-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DLGAP1-AS2 regulates miR-503/cyclin D1 to promote cell proliferation in non-small cell lung cancer

Abstract: Background LncRNA DLGAP1-AS2 plays an oncogenic role in glioma, while its role in other cancers is unknown. This study aimed to study the role of DLGAP1-AS2 in non-small cell lung cancer (NSCLC). Methods Expression of DLGAP1-AS2 in NSCLC and paired non-tumor tissues from 64 NSCLC patients and the prognostic value of DLGAP1-AS2 for NSCLC were analyzed by performing a 5-year follow-up study. The interaction between DLGAP1-AS2 and miR-503 was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Recent studies also reported the upregulation and prognostic value of DLGAP1-AS2 in several cancer types. Similar tumor-promoting functions have also been observed in multiple cancer types, including rectal cancer [19][20][21][22][23][24][25][26]. For example, a recent study conducted by Zeng et al reported that DLGAP1-AS2 promotes the radioresistance in rectal cancer stem cells through regulating the E2F1-CD151 axis [27].…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies also reported the upregulation and prognostic value of DLGAP1-AS2 in several cancer types. Similar tumor-promoting functions have also been observed in multiple cancer types, including rectal cancer [19][20][21][22][23][24][25][26]. For example, a recent study conducted by Zeng et al reported that DLGAP1-AS2 promotes the radioresistance in rectal cancer stem cells through regulating the E2F1-CD151 axis [27].…”
Section: Discussionmentioning
confidence: 56%
“…23,24,26 Notably, several studies reported that dysregulated miR-503 is involved in tumor progression by suppressing a variety of target genes in lung cancer. [27][28][29][30][31] In this work, we first investigated the role of miRNAs in mediating the phenotypic change of lung cancer cells in the context of acquiring resistance to targeted therapies and revealed that miR-503 significantly dampens cell migration and invasion, EMT, and in vivo lung metastasis. Notably, we disclosed the new action of miR-503 by identifying PTK7, an important player in collective migration, as a novel target of miR-503.…”
Section: Discussionmentioning
confidence: 99%
“…Those miRNAs that exhibit NSCLC-specific expression patterns have the potential to be leveraged for the sensitive and specific diagnosis of this cancer type [ 24 ]. miR-503 was found downregulated in NSCLC tissues, and overexpression of miR-503 suppressed NSCLC cell multiplication [ 25 , 26 ]. miR-510 is a potential oncogene in NSCLC through regulating SRCIN1 [ 27 ] and PTEN [ 28 ].…”
Section: Discussionmentioning
confidence: 99%